Software system integration - Middleware - an overview - Asif, Seemal; Webb, Philip (Foundation of Computer Science, 2015)
The integration of different softwares written in different language and based on different platforms can be tricky. In that situation a middleware is necessary to enable the communication between different softwares. The middleware enables the software system not only to share data but also share the services. This paper gives an overview of some of middleware technologies which can be used to integrate different software systems.
Keywords: Middleware; SOA; SOAP; Web Services